2020
DOI: 10.3390/ijms21207783
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Infantile Facioscapulohumeral Muscular Dystrophy: A Timely Review

Abstract: Facioscapulohumeral muscular dystrophy (FSHD)—the worldwide third most common inherited muscular dystrophy caused by the heterozygous contraction of a 3.3 kb tandem repeat (D4Z4) on a chromosome with a 4q35 haplotype—is a progressive genetic myopathy with variable onset of symptoms, distribution of muscle weakness, and clinical severity. While much is known about the clinical course of adult FSHD, data on the early-onset infantile phenotype, especially on the progression of the disease, are relatively scarce. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…The correlation is clearer with very short repeat arrays, with severe and progressive respiratory failure requiring ventilatory support reported very rarely in infantile-onset cases. 37,43 In our series, the repeat unit size was relatively similar between patients with and without abnormal FVC.…”
Section: Discussionsupporting
confidence: 56%
“…The correlation is clearer with very short repeat arrays, with severe and progressive respiratory failure requiring ventilatory support reported very rarely in infantile-onset cases. 37,43 In our series, the repeat unit size was relatively similar between patients with and without abnormal FVC.…”
Section: Discussionsupporting
confidence: 56%
“…It is notable that four of eight patients with early-onset FSHD had atrial enlargement or ventricular hypertrophy, which had not been reported in other cohorts. Previous studies had identified conduction abnormalities in early-onset FSHD, but it remains uncertain whether these abnormalities occur at a higher frequency in early-onset FSHD compared to those with a more classical age of onset ( 20 , 23 , 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…FSHD is inherited in an autosomal dominant manner; however, approximately 30% are de novo cases. Additionally, there is a high frequency of somatic mosaicism [97]. FSHD typically presents with weakness in one or more of these facial muscles, the stabilizers of the scapula, or the dorsiflexors of the foot.…”
Section: Facioscapulohumeral Muscular Dystrophy (Fshd)mentioning
confidence: 99%